SOFT CORAL (Sinularia sp.) EXTRACTS WITH ANTIBACTERIAL ACTIVITY - Wendy Alexander Tanod; Anita Treisya Aristawati; Masteria Yunovilsa putra; Muliadin Muliadin (Journal Omni-Akuatika, 2018)
There is a growing need for new antibacterial agents, in particular because many antibiotics are becoming ineffective due to the emergence of resistant bacterial strains. Soft corals of the Genus Sinularia, Family Alcyoniidae, have potential as a source of terpenoid and steroid compounds with antibacterial activity. These corals may vary in external morphology (shape, colour, size).The aim of this research was to identify extracted fractions with high antibacterial activity. Sinularia sp. specimens were extracted, fractionated based on solvent polarity, and tested for antibacterial bioactivity against pathogenic bacteria (Escherichia coli and Staphylococcus aureus). Antibacterial activity of the three fractions varied in strength. The dichloromethane fraction showed strong antibacterial activity, inhibiting S. aureus and E. coli growth at a concentration of 1 mg ml-1, while the ethyl acetate and ethanol fractions were effective at 10 mg ml-1 and 100 mg ml-1, respectively.